Childhood family environment and systemic haemodynamics in adulthood : the Cardiovascular Risk in Young Finns Study - Kähönen, Erika; Lehtimäki, Terho; Raitakari, Olli T.; Kähönen, Mika; Hutri, Nina; Keltikangas-Järvinen, Liisa; Saarinen, Aino (Sage, 2025)
Aims: Childhood family environment is associated with adulthood health behaviours and cardiovascular health, but limited data are available concerning the relationship between childhood family environment and adulthood haemodynamic determinants of blood pressure. We evaluated how childhood family environment predicts adulthood systemic haemodynamics.
Methods: The sample came from the Cardiovascular Risk in Young Finns Study (n=1554-1620). Childhood family environment (1980) was assessed with four cumulative risk scores: socioeconomic family risk, risky emotional family atmosphere, stressful life events, and parents' risky health behaviours. Haemodynamic outcomes in 2007 (participants being 30-45 year-olds) included stroke volume index, systemic vascular resistance index, cardiac output index and heart rate. Analyses were adjusted for childhood (1980) cardiovascular risk factors (high-density lipoprotein and low-density lipoprotein cholesterol, triglycerides, insulin, body mass index and systolic blood pressure); and adulthood (2007) health behaviours (alcohol consumption, smoking, physical activity); and finally for adulthood cardiovascular risk factors.
Results: When adjusted for age and sex, high socioeconomic family risk predicted lower stroke volume index (P=0.001), higher heart rate (P=0.001) and higher systemic vascular resistance index (P=0.030). These associations remained after controlling for childhood cardiovascular covariates or adulthood health behaviours (P⩽0.02 for all) but diluted after controlling for adulthood cardiovascular risk factors. The other childhood cumulative risk scores (stressful life events, risky emotional atmosphere, or parents' risky health behaviour) did not predict adulthood haemodynamic outcomes.
Conclusions: High childhood socioeconomic family risk predicted adulthood haemodynamic outcomes independently of childhood cardiovascular risk factors and adulthood health behaviours, while other childhood psychosocial adversities were not associated with cardiovascular function in adulthood.